Undernutrition and its predictors among tuberculosis patients in Southwest Ethiopia - Shifera, Nigusie; Yosef, Tewodros (Frontiers in Nutrition, 2024)
Background Adult tuberculosis (TB) patients experience significant undernutrition globally, especially in developing countries. While some studies have explored the prevalence and factors influencing undernutrition in this group, comprehensive large-scale investigations covering diverse health facilities and populations are lacking. This study aims to evaluate the prevalence of undernutrition and its associated factors among adult TB patients in public hospitals in southwest Ethiopia. Method An institution-based cross-sectional study design was conducted from March 01 to April 15, 2023, in public hospitals in the southwest region, of Ethiopia. A total of 239 adult TB patients who were directly observed in TB treatment were selected via systematic sampling. A structured questionnaire was adapted from a review of different literature. Data were cleaned and entered into EPI info version 7, then analyzed with SPSS Version 22. A bivariable analysis was done to evaluate associations at (p < 0.25), and then multiple logistic regression models were computed to identify independent predictors of undernutrition among TB patients at (p < 0.05). Results A total of 239 respondents participated with a response rate of 100%. The prevalence of undernutrition among adult TB patients was 43.93%. Of the 239 TB patients, the majority (91.6%) were new TB cases. Family size >5 (AOR 3.23 [1.16–9.01]), household average income <2,000 birr (AOR 5.64 [2.12–14.99]), type of TB (AOR 2.8 [1.25–6.51]), and positive HIV status of the study participant (AOR 3.23 [1.16–9.01]) were the independent predictors of undernutrition among adult TB patients. Conclusion and recommendations Undernutrition among adult tuberculosis (TB) patients is notably high compared to other settings. Key predictors include a family size greater than five, a monthly income below 2,000 birr, HIV status, and pulmonary TB. Early screening and diagnosis of undernutrition, along with nutritional interventions, should be integrated into the routine care for all adult TB patients.